Knowledge about Emergency Contraceptive Pills Among Women Attending OPD of Tertiary Care Hospital - Zill-E-Huma, Ghazala Iftikhar, Asma Hanif, Shagufta Jabbar, Amna Asif, Kamran Ullah Khan, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Unintended pregnancy is one among social problems in every country in this era. Emergency contraceptive pills are used for avoidance of pregnancy after unprotected coitus in a woman who is not using any regular method of contraception. The aim of this cross-sectional study was to ascertain the knowledge about emergency contraception among women attending OPD of Social Security teaching hospital, Multan Road, Lahore. Methods: A cross-sectional study was carried out in OPD of Gynaecology Department, Social Security Teaching Hospital, Multan Road Lahore from 1st May 2023 to 31st October 2023. A total of 350 women were enrolled. Knowledge of emergency contraceptive pills such as dose, correct timing of administration, efficacy and side effects were noted. Adequacy of knowledge was considered if 4 or more questions were answered correctly. Results: Mean age of the women was 20.9±1.7 12% had parity 0-1, 25.4% had parity 2-4 and 62.6% had parity 5-7. About 10.5% of women showed adequate knowledge of emergency contraceptive pills (ECP). Conclusion: Most of women lack the knowledge about emergency contraceptive pills, whereas some women had misunderstanding regarding their use. Keywords: Emergency contraception, Unwanted pregnancy, Family planning